Social and Economic Impact of Measurable Fishing Policies on Fishermen in North Aceh Regency - Riyandhi Praza; Rizki Yunanda; Dedi Fariadi; Sahran Saputra; Dewi Astuti (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2024)
The measured fishing policy, or catch share, aims to manage marine resources sustainably by providing special quotas to fishermen, but its implementation in North Aceh Regency shows complex social and economic impacts. While these policies can reduce overfishing and improve planning for fishers' activities, potential inequalities in quota distribution can exacerbate economic inequality, with large fishers better able to control quotas than small or traditional fishers. This can affect the social structure within the fishing community and create tension. While there is potential to strengthen cooperation between fishers and increase incomes, the success of these policies relies heavily on fair and inclusive planning to ensure optimal economic and social benefits and sustainability of marine resources. Theoretical perspective on the impact of socio-economic change. Data collection was carried out through Live in, observation, in-depth interviews and the use of documents. The data analysis process is carried out interactively through stages; Data collection, data verification, data patterns, data coding, data thematic networks, meaning and conclusion drawn. The results of this study show that the measured fishing policy in North Aceh aims to preserve marine resources through the regulation of catch quotas. Despite the impact on fishermen's income and society, this policy has the potential to provide long-term benefits if managed properly, through increased fish stocks, stable incomes, and fisher participation.